Բլոգների քաղաքական ազդեցության մեծացման առանձնահատկությունները ՀՀ-ում - Էրիկ Ղազարյան (ՀՀ ԳԱԱ հրատ.)
В данной работе автор представляет особенности формирования блогов в Армении и увеличения их влияния на политику. Ghazaryan in this article presents the emergence of social blogs in RA together with the aspects of their intensifying impact on the policy of the country.
Keywords: Bibliography; Political science; Information resources